2019
DOI: 10.1017/s1041610219001066
|View full text |Cite
|
Sign up to set email alerts
|

Independent and joint effects of vascular and cardiometabolic risk factor pairs for risk of all-cause dementia: a prospective population-based study

Abstract: Objectives:To assess independent and joint effects of pairs of vascular and cardiometabolic risk factors (VCMRFs) in relation to risk of all-cause dementia.Design:Population-based longitudinal cohort study of cognitive impairment. We used an algorithm to select pairs of VCMRFs and tested their joint effects in time-dependent Cox models. We used attributable proportions (AP) to measure the proportion of risk from interactions beyond any additive effect.Setting:Economically depressed small-town population.Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…Considering not all ApoE4 carriers will develop dementia, other factors beyond the inheritance of an ApoE4 allele must modulate its impact on cognitive decline, determining which carriers will be diagnosed with the disease. Importantly, this study by Shaaban et al (2019) provides novel evidence that cerebrovascular health may be particularly important for ApoE4 carriers because strokean indication of poor cerebrovascular health and ApoE4 were found to act synergistically to increase dementia risk. That is, while each of these factors independently increased dementia risk, their combined effects were stronger than would be expected by simply adding each individual effect.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Considering not all ApoE4 carriers will develop dementia, other factors beyond the inheritance of an ApoE4 allele must modulate its impact on cognitive decline, determining which carriers will be diagnosed with the disease. Importantly, this study by Shaaban et al (2019) provides novel evidence that cerebrovascular health may be particularly important for ApoE4 carriers because strokean indication of poor cerebrovascular health and ApoE4 were found to act synergistically to increase dementia risk. That is, while each of these factors independently increased dementia risk, their combined effects were stronger than would be expected by simply adding each individual effect.…”
mentioning
confidence: 77%
“…For example, Martin et al (2019) reported that heart problems were associated with lower Mini-Mental State Examination scores among U.S. but not Japanese centenarians. In the current issue, Shaaban et al (2019) extend upon these studies by providing evidence that, at least in their predominantly white U.S. sample, CHF is one of the most important risk factors for the development of all-cause dementia. Strikingly, the joint effect of CHF and stroke increased risk of dementia almost 50 times compared to participants who had neither risk factor, which was significantly higher than the predicted additive effect of these two factors.…”
mentioning
confidence: 80%
“…This HBF improvement could help prevent or delay AD for these individuals at highest known genetic risk, considering the growing evidence that CBF reductions precede measurable cognitive decline [1, 44] and likely contribute causally to dementia pathogenesis [3, 45-47]. Additionally, APOE4 carriers have been shown to experience an accelerated age-related CBF decline [48, 49], and some studies suggest cerebrovascular dysfunction may act synergistically with the APOE4 allele to promote cognitive decline [12, 50]. If true, this would mean CBF maintenance is even more important for APOE4 carriers than non-carriers in order to prevent dementia, strengthening the clinical relevance of our current findings.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest known genetic risk factor for AD, the APOE4 allele, may act synergistically with poor vascular health to increase dementia risk [12-18]. This suggests interventions that improve systemic vascular health may be particularly beneficial for APOE4 carriers [19].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of risk factors and preventative strategies are primary objectives in research on impaired cognitive functioning in older adults (Brayne, 2007;Treichler and Jeste, 2019). Indeed, general health-related risk factors have been identified during midlife and old age (Launer, 2005;Launer, 2007;Kaufman and Perales-Puchalt, 2019;Lee et al, 2019;Shaaban et al, 2019;Tu et al, 2020;Walker et al, 2019). Nonetheless, a recent shift has seen studies that examine the role of early-life risk factors to increment current knowledge of risk factors (Grainger et al, 2019;Launer, 2007;Whalley et al, 2006;Williamson and Leroi, 2019).…”
Section: Introductionmentioning
confidence: 99%